Examining Student Perceptions of Genially-Based Learning Media Integrated with Problem-Based Learning to Enhance English Reading Comprehension - Hidayat, Wahyu; Napitupulu, Efendi; Simbolon, Naeklan (FINGER : Jurnal Ilmiah Teknologi Pendidikan, 2025)
Background: In the digital age, English language instruction requires innovative approaches to improve student engagement and outcomes. Traditional teaching methods often fail to foster motivation and active participation, particularly in reading comprehension.Aims: This study focuses on students' feedback on the developed product an interactive learning medium using the Genially platform, integrated with a Problem-Based Learning (PBL) approach, without covering the full product development process or evaluating its impact on reading comprehension.Methods: A qualitative descriptive method was employed, focusing on student perceptions of the developed media. Data were collected through structured questionnaires and open-ended responses from students at SMP Negeri 3 Pantai Labu. The analysis used descriptive statistics and thematic categorization to evaluate aspects such as content quality, usability, design, and interactivity.Result: Findings showed consistently high ratings across all evaluation aspects, with an overall average score of 0.94. Students reported increased motivation, better comprehension, and a more enjoyable learning experience. The Genially-based media was perceived as visually appealing, user-friendly, and effective in facilitating independent and collaborative learning through real-world problem contexts.Conclusion: The integration of Genially and PBL in English instruction proved to be feasible, practical, and positively received by students. It offers a promising alternative to conventional methods and supports a more engaging, student-centered learning environment.